2020
DOI: 10.1111/jace.17506
|View full text |Cite
|
Sign up to set email alerts
|

On fast LuAG:Ce scintillation ceramics with Ca2+ co‐dopants

Abstract: Scintillation materials, as optical functional materials that can absorb high-energy rays or particles and convert them into low-energy photons, have been successfully applied in various application fields. 1,2 Over the past few decades, as the requirements for scintillation properties in medical imaging and high energy physics (HEP) experiments have become more stringent, a variety of scintillation materials have been developed. Among them, lutetium aluminum garnet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Several strategies have been proposed to reduce carrier trapping and create additional routes of carrier transport to cerium ions in garnets by aliovalent co-doping with Mg 2+ , Ca 2+ , Li + , and transition metals. Defect engineering by Mg 2+ co-doping appeared to be the most promising and contributed to the acceleration of luminescence decay and increasing light yield. The Ce 4+ –Mg 2+ complexes that form due to charge compensation create an efficient channel of electron and hole capture by Ce 3+ luminescence centers. , …”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been proposed to reduce carrier trapping and create additional routes of carrier transport to cerium ions in garnets by aliovalent co-doping with Mg 2+ , Ca 2+ , Li + , and transition metals. Defect engineering by Mg 2+ co-doping appeared to be the most promising and contributed to the acceleration of luminescence decay and increasing light yield. The Ce 4+ –Mg 2+ complexes that form due to charge compensation create an efficient channel of electron and hole capture by Ce 3+ luminescence centers. , …”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained results, it can be concluded that boron‐doped ceramics have a shorter decay time, which is required for scintillators. The decay times of this synthesized ceramic are one of the shortest compared with the work of other scientists (for YAG:Ce this varies from 58 to 60 ns, for LuAG this is from 54 to 50 ns) [31–33]. Although scintillation decay times have not been measured in this work, it can be argued from the literature that for both photoluminescence and scintillation decay times (decreases and increases), specific trends and values correlate [17, 34–36].…”
Section: Resultsmentioning
confidence: 80%
“…The reduction in the time constant can potentially be achieved through co-doping these materials with divalent ions. The effect has been well-demonstrated in LuAG, where Mg 2+ or Ca 2+ ions have suppressed slower components of the decay times 21 , and was recently explored in GGAG 22,23 . With faster rise and decay time constants, Gd-garnets could compete with LSO for the PET market.…”
Section: Ce Doped Garnetsmentioning
confidence: 87%